The changing role of agriculture with economic structural change: The case of China - Zhang, Yumei; Diao, Xinshen (Elsevier, 2020)
We analyze the implication of structural change to the evolving role of agriculture using China as an example. By combining a growth decomposition exercise with Input-Output (IO) and CGE model analyses using China's seven input-output tables (IOTs) in 1987–2017, the evolving role of the agriculture is quantitatively measured. The growth decomposition analysis shows that between 1978 and 2017, China doubled the size of its total labor force, while the absolute number of agricultural workers falls in this period. Rising labor productivity in agriculture has led to rapid agricultural growth without increasing agricultural employment, allowing agriculture to indirectly contribute to the economywide productivity growth through structural change. The measurement of economic integration using an IO approach helps to explain why China's rapid structural change has been accompanied by similar rapid productivity growth within each sector. The general equilibrium effect of structural change on the evolving role of agriculture is further assessed using two CGE models representing the initial (1987) and end (2017) years of a period of 30 years. Similar agricultural productivity shock induces a smaller economywide gain in 2017 than in 1987 in the CGE models, while the gap in the general equilibrium gain between these two years is much smaller than the difference in agriculture's size of the economy in the two years because of stronger linkages between agriculture and the rest of the economy in 2017. About 0.5 unit additional nonagricultural value-added is associated with a unit agricultural value-added increase in 1987, while additional gains in nonagricultural value-added rise to 2.7 unit in 2017. Our analysis of economic integration and implication of structural change to the evolving role of agriculture emphasizes the supply side role for sustainable growth in which agriculture continues to play an important but different role from the past when the demand side effects were stronger. Policies to strengthen supply side linkages have been emphasized in the recent years in China. Exploring further integration between agriculture and the rest of the economy should be part of the new growth strategy.